Agama, dominasi, dan prasangka: Hubungan antara orientasi dominasi sosial dan meta-prasangka pada kelompok agama minoritas - Firmansyah, Muhammad Reza; Mashuri, Muhammad Fath; Rahmanawati, Ainin; Kurniawan, Wawan (Konsorsium Psikologi Ilmiah Nusantara, 2026)
The dominance behavior of certain religious groups is often associated with prejudice toward other religious groups. This condition may generate negative evaluations, in which majority religious groups are perceived as more dominant than minority groups. This study aimed to examine the relationship between social dominance orientation and meta-prejudice among religious minority groups in Indonesia. Using a quantitative correlational design, this study involved 218 participants from religious minority groups (non-Muslims). The correlation analysis revealed a significant positive relationship between social dominance orientation and meta-prejudice. More specifically, significant relationships were found across all four dimensions of social dominance orientation (pro-dominance, anti-dominance, pro-egalitarianism, and anti-egalitarianism) and meta-prejudice. These findings suggest that social dominance orientation is associated with how minority groups perceive prejudice from majority groups. The study highlights the importance of strengthening interreligious tolerance and developing psychosocial interventions to reduce prejudice in multicultural societies.